The connection between Capital structure and performance: Does firm size matter? - Marwan Mansour; Mo’taz Kamel Al Zobi; Ahmad Al-Naimi; Luay Daoud (Investment Management & Financial Innovations, 2023)
The purpose of this paper is to empirically investigate the impact of capital structure decisions on firm performance in Jordan (2010–2018), as well as the extent to which firm size matters in the capital structure-performance relationship. The dependent variable was market share. The main independent variables were the book value of total debt ratios, and firm-specific factors such as firm size, firm age, firm growth, and market-to-book value of equity served as control variables. This study used a quantitative research method using panel data analysis of 830 firm-year observations. Random effects model was employed to analyze the capital structure-performance nexus. To infer correctly, the main analysis was re-examined using the generalized method of moment estimator to overcome possible endogeneity concerns. After controlling for endogeneity and firm heterogeneity, this study finds that the book value of capital structure has a signiﬁcantly positive relation to a firm’s market share. Hence, every one unit increase in the book value of total debt ratios will increase market share by 4.77%. The firm size, sales growth, and market-to-book value of equity had a signiﬁcantly positive association with market share. Hence, every one unit increase in firm size, growth and market-to-book equity ratio will increase a firm’s market share by 8.84%, 2.06%, and 2.15%, respectively, but surprisingly, firm age did not meaningfully contribute to operating performance. Another important finding was that the strength of a positive relationship between the book value of total debt ratios and market share depends on the size of a firm and is mostly higher for larger-sized firms. Hence, every one unit increased in the book value of total debt ratios for large firms will increase market share by 10.58%.